PENGARUH PENAMBAHAN EKSTRAK ENZIM CAIRAN RUMEN DOMBA PADA KOMPONEN SERAT KASAR, KANDUNGAN ASAM FITAT TEPUNG DAUN LAMTORO GUNG (Leucaena leucocephala) - Indira Fitriliyani (Faculty of Fisheries and Marine Resources of Lambung Mangkurat University-South Kalimantan, 2019)
The aim of this experiment was to evaluate the nutrient quality of leucaena leaf meal(LLM) with addition of sheep rumen liquor enzyme for nile tilapia feed which incubated 24 hours (in vitro); This experiment was designed in completely randomized design with 6 treatments and 3 replications each with different level of enzyme addition (0; 20; 40;60; 80; and 100 ml/kg LLM). Results of the experiment showed that nutrient quality of LLM with addition of sheep rumen liquor enzyme which incubated for 24 hours, wheresignificantly affected (P<0.05) on decrease of crude fiber (53,640%), NDF, ADFcomponent and phytic acid (68,088%). Over all conclusion is a great potential for using sheep rumen liquor enzyme for improving nutrition quality of leucaena leaf meal.